Spermidine and spermine exert protective effects within the lung. Issue 4 (21st July 2021) - Wawrzyniak, Marcin; Groeger, David; Frei, Remo; Ferstl, Ruth; Wawrzyniak, Paulina; Krawczyk, Krzysztof; Pugin, Benoit; Barcik, Weronika; Westermann, Patrick; Dreher, Anita; Scharl, Michael; Jutel, Marek; et al.
Abstract: Asthma is a heterologous disease that is influenced by complex interactions between multiple environmental exposures, metabolism, and host immunoregulatory processes. Specific metabolites are increasingly recognized to influence respiratory inflammation. However, the role of protein‐derived metabolites in regulating inflammatory responses in the lung are poorly described. The aims of the present study were to quantify polyamine levels in bronchoalveolar lavages (BALs) from healthy volunteers and asthma patients, and to evaluate the impact of each polyamine on inflammatory responses using in vitro models and in a house dust mite (HDM)‐induced respiratory allergy model. Spermidine levels were decreased, while cadaverine levels were increased in BALs from asthma patients compared to healthy controls, using Ultra Performance Liquid Chromatography (UPLC). Both spermine and spermidine inhibit lipopolysaccharide (LPS)‐induced cytokine secretion from human peripheral blood mononuclear cells (PBMCs) and dendritic cells (DCs) in vitro. In addition, oral gavage with spermine or spermidine modulate HDM‐induced cell infiltration, cytokine secretion, and epithelial cell tight junction expression in murine models. Spermidine also reduces airway hyper‐responsiveness. These results suggest that modulation of polyamine metabolism, in particular spermidine, is associated with respiratory inflammation and these molecules and pathways should be further explored as biomarkers of disease and potential targets for novel therapies. Abstract : Spermine and spermidine display anti‐inflammatory effects using in vitro models and protect against house dust mite (HDM) extract‐induced airway inflammation in murine models.